Is inequality in subjective well-being meritocratic? Danish evidence from linked survey and administrative data - Claus Thustrup Kreiner; Isabel Skak Olufsen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
This paper decomposes inequality in subjective well-being into inequality due to socioeconomic background (SEB) and meritocratic inequality due to differences in individual merits such as school performance. We measure the meritocratic share of well-being, defined as the share of explained variation in life satisfaction attributable to variation in merits not related to SEB. The empirical evidence from Denmark combines survey information on well-being with administrative data on individual characteristics. We find systematic differences in wellbeing already in early adulthood, where differences in economic outcomes are not yet visible. At age 18-19, about 40 percent of the inequality in well-being is meritocratic. The role of merits rises to 65-85 percent in midlife (age 40-55), where it is also higher than the role of merits in income inequality. The positive conclusions that inequality in well-being is more meritocratic than income inequality and more meritocratic as people grow older get support by corresponding results using an equal opportunity approach.
Keywords: I31; J62; D30; D63; 330; Subjective well-being; inequality; intergenerational mobility